Simulating magnetic field of a ferromagnetic pipe underwater in COMSOL Multiphysics; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Soltanova D.; Baranov P.; Baranova V. E. Vitaliya Evgenyevna; Chudinova A. I. Alena Igorevna (Electronic engineering, 2015)
Title screen